Poliéster na construção civil - OLIVEIRA, Raquel Agostinho dos Santos; PEREIRA, Maria Clara Araújo (181, 2025)
Este artigo explora a viabilidade de reutilizar resíduos de poliéster da indústria têxtil no desenvolvimento de tijolos sustentáveis para a construção civil, visando reduzir o descarte inadequado de resíduos têxteis em aterros sanitários. Apesar do poliéster ser derivado do petróleo e ter uma produção com emissão de poluentes, sua reutilização oferece uma alternativa promissora. O artigo aborda a definição, história e aplicações do poliéster na construção civil, apresentando exemplos como a startup FabBRICK, que transforma resíduos têxteis em tijolos ecológicos. O processo de fabricação de tijolos com poliéster é similar ao de tijolos solo-cimento, com a adição de poliéster triturado à mistura, melhorando a resistência, o isolamento térmico e o desempenho acústico. A Avaliação do Ciclo de Vida (ACV) é essencial para validar a viabilidade ambiental, demonstrando que a reutilização de resíduos reduz a demanda por recursos naturais e a emissão de gases de efeito estufa. A conclusão é que o desenvolvimento de tijolos sustentáveis a partir de resíduos de poliéster é uma solução inovadora para mitigar impactos ambientais e promover a economia circular na construção civil.

This article explores the feasibility of reusing polyester waste from the textile industry in the development of sustainable bricks for civil construction, aiming to reduce the improper disposal of textile waste in landfills. Despite polyester being derived from petroleum and having a production process that emits pollutants, its reuse offers a promising alternative. The article addresses the definition, history, and applications of polyester in civil construction, presenting examples such as the startup FabBRICK, which transforms textile waste into ecological bricks. The manufacturing process of bricks with polyester is similar to that of soil-cement bricks, with the addition of shredded polyester to the mixture, improving resistance, thermal insulation, and acoustic performance. The Life Cycle Assessment (LCA) is essential to validate environmental feasibility, demonstrating that the reuse of waste reduces the demand for natural resources and the emission of greenhouse gases. The conclusion is that the development of sustainable bricks from polyester waste is an innovative solution to mitigate environmental impacts and promote the circular economy in civil construction.
Polyester in civil construction
Keywords: Construção civil; Poliéster; Indústria têxtil; Ambiente e Saúde